Providing a Causal Model of Strategic Policies in Water Crisis Management Based on The Statement of the Second Phase Of The Revolution - Hamidreza Vasheghani farahani; mohammad reza mardani; ehsan sadeh; ZEINOLABEDIN AMINISABEGH (توسعه اجتماعی, 2022)
Currently, the water crisis is one of the most complex public issues in the country, and its management has become one of the country's top priorities. The most important issue in this situation is recognizing the most basic strategic policies as a key policy to resolve the water crisis. But in this regard, despite its importance and emphasis in the second phase of the revolution, there is a study gap. Therefore, the present study was conducted with the aim of providing a causal model of strategic policies in water crisis management based on the statement of The Second Phase of the Revolution. This research was applied research in terms of purpose and also mixed research (quantitative-qualitative) in terms of research method, in which theoretical and experimental foundations were examined to determine the indicators. This research was of the type of applied research in terms of purpose and also of the type of mixed research (quantitative-qualitative) in terms of research method, in which theoretical and experimental foundations were examined to determine the indicators. The obtained criteria (fuzzy Delphi method) based on expert interviews and using fuzzy Demetel technique was examined to determine the causal relationships between strategic policies. The results show that reducing the dependence of equipment imports from abroad and the use of domestic capacities is the most important among all elements and categories. On the other hand, the following items have the highest impact on the water crisis management model, respectively: 1. Monitoring and evaluating the extent of governance duties and avoiding government ownership; and 2. Creating intelligent infrastructure in the network covered and integrated management with emphasis on hardware and software infrastructure.